Of Parts and Politics: Onticology and Queer Politics - Bryant, Levi R. (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Levi R. Bryant Title (English): Of Parts and Politics: Onticology and Queer Politics Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 13-28 Page Count: 15 Citation (English): Levi R. Bryant, “Of Parts and Politics: Onticology and Queer Politics,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 13-28.